Networked Carbon Markets : Mitigation Action Assessment Protocol - World Bank Group (World Bank, Washington, DC, 2016)
This Mitigation Action Assessment Protocol (MAAP) is proposed as a key tool for achieving transparency in how these climate actions are designed and how they compare in terms of mitigation value. The long-term goal is to have the MAAP serve as an internationally accepted system for comparing carbon assets and, eventually, the trade potential and exchangeability of carbon credits. Such a framework does not yet exist, but is a much-needed step in effectively and efficiently addressing climate change on a global scale. The MAAP focuses on the mitigation value of a particular type of carbon asset—carbon credits. Carbon credits are generated when jurisdictions reduce carbon emissions below a baseline level. The increasing number and diversity of mitigation actions that are emerging has accelerated the need for independent analyses of the various initiatives and the mitigation value of the carbon credits they generate. The approach presented in this document falls within the broader scope of work from the World Bank Group’s Networked Carbon Markets (NCM) initiative. The proposed MAAP can be applicable to a range of mitigation actions, as well as the evolution of those actions over time. As already stated, the ultimate goal of the MAAP is to compare carbon credits from jurisdiction to jurisdiction and inform linking decisions. However, in the short term, given the current efforts by different jurisdictions toward the design and implementation of mitigation actions, the MAAP is first and foremost intended to be a tool to facilitate prioritization, benchmarking, and better-designed mitigation actions. It can also be used to assist different stakeholders in defining the elements of a robust mitigation action and the level of development expected of the different components required for an acceptable level of confidence in the success of the action. The MAAP could help inform the design of regulatory instruments, such as Nationally Appropriate Mitigation Actions (NAMAs). The assessment of the mitigation value is important if the carbon credits generated from the mitigation action are intended to be traded. The MAAP also proposes an approach to assess the mitigation value of an intervention, which is then not only determined by its isolated impact (carbon integrity) but also by its relevance in the context of jurisdictional effort. This combines analysis of the creditability of the actions implemented and the relative contribution to the global emission reduction effort, which is only likely to be relevant if the carbon assets are to be traded internationally. This examination is done within the specific context of the relative effort that each jurisdiction can actually make to contribute to climate change mitigation.